Diagnostic potential of dentatorubrothalamic tract analysis in progressive supranuclear palsy. (April 2018) - Seki, Morinobu; Seppi, Klaus; Mueller, Christoph; Potrusil, Thomas; Goebel, Georg; Reiter, Eva; Nocker, Michael; Steiger, Ruth; Wildauer, Matthias; Gizewski, Elke R.; Wenning, Gregor K.; Poewe, Werner; et al.
Abstract: Background: The differentiation of progressive supranuclear palsy-parkinsonism (PSP-P) from Parkinson's disease (PD) remains a major clinical challenge. Objectives: To evaluate the diagnostic potential of observer-independent assessments of microstructural integrity within infratentorial brain regions to differentiate PSP-Richardson's syndrome (PSP-RS), PSP-P and PD. Methods: 3T MRI parameters of mean diffusivity, fractional anisotropy, grey and white matter volumes from patients with PSP-RS (n = 12), PSP-P (n = 12) and mean disease duration of 2.4 ± 1.7 years were compared with PD patients (n = 20) and healthy controls (n = 23) by using statistical parametric mapping and the spatially unbiased infratentorial template. Subsequently MRI measurements of the dentatorubrothalamic tract were determined observer-independently by a validated probabilistic infratentorial atlas. The impairment of gait and postural stability was evaluated by a sum-score derived from the Unified Parkinson Disease Rating Scale. Results: Significant mean diffusivity increases, fractional anisotropy decreases and corresponding volume loss were localized in mesencephalic tegmentum, superior cerebellar peduncle, decussation of superior cerebellar peduncle and dentate nucleus in PSP-RS and PSP-P compared to PD and healthy controls. Altered microstructural integrity of the dentatorubrothalamic tract in PSP-RS was significantly more pronounced compared to PSP-P and correlated significantly with the gait and postural stability sum-score. Linear discriminant analysis identified diffusion tensor imaging measures of the dentatorubrothalamic tract and the gait and postural stability sum-score to classify correctly 95.5% of PRP-RS, PSP-P and PD patients. Conclusions: Observer-independent analysis of microstructural integrity within the dentatorubrothalamic tract in combination with assessments of gait and postural stability differentiate PSP-P from PSP-RS and PD in early to moderately advanced stages. Highlights: We applied voxel-based and atlas-based ROI analyses to MRI in PSP-RS, PSP-P and PD. Both PSP subtypes showed altered DTI within the dentatorubrothalamic tract (DRTT). PSP-RS demonstrated more pronounced DTI changes in the DRTT compared to PSP-P. DTI of DRTT correlated with impairments of gait and postural stability in PSP-RS. DTI of DRTT and gait and postural stability score could classify 95% of patients.